Animasi Interaktif Pembelajaran Huruf dan Angka Menggunakan Model ADDIE - Bakhri, Syamsul (Universitas Nusantara PGRI Kediri, 2019)
The use of technology in learning media is very necessary for all educational institutions. Creating a pleasant learning atmosphere through multimedia means in the form of interactive animations. It was felt effective to increase children's learning interest in recognizing letters and numbers at TK RA Nurul Iman Jakarta. Use the type of research and development with the ADDIE model. Calculation of the app's feasibility to produce interactive animations that fit your needs. The purpose of making this learning media helps students to be able to more easily understand and understand and not feel bored in learning to start from letters and numbers and how to pronounce them. After the learning process, students will work on the quiz and there will also be games to make the child's thinking speed better. In addition, this application can help teachers in the teaching and learning process that is considered very boring, with an average value of 82.6% showing this interactive animation application is very fun for the media to learn the introduction of numbers and letters.